Validating new limits for human thermoregulation - Robert D. Meade; Fergus K. O’Connor; Brodie J. Richards; Emily J. Tetzlaff; Katie E. Wagar; Roberto C. Harris-Mostert; Theodore Egube; James J. McCormick; Glen P. Kenny (Proceedings of the National Academy of Sciences, 2025)
Recent projections suggest that large geographical areas will soon experience heat and humidity exceeding limits for human thermoregulation. The survivability limits modeled in that research were based on laboratory studies suggesting that humans cannot effectively thermoregulate in wet bulb temperatures (T wb ) above 26 to 31 °C, values considerably lower than the widely publicized theoretical threshold of 35 °C. The newly proposed empirical limits were derived from the T wb corresponding to the core temperature inflection point in participants exposed to stepped increases in air temperature or relative humidity in a climate-controlled chamber. Despite the increasing use of these thermal-step protocols, their validity has not been established. We used a humidity-step protocol to estimate the T wb threshold for core temperature inflection in 12 volunteers. To determine whether this threshold truly demarcates the T wb above which thermoregulation is impossible, each participant was subsequently exposed to T wb above (~33.7 °C, T above ) and below (~30.9 °C, T below ) their respective inflection point (~32.3 °C, T wb ) for up to 9 h (in random order). Core temperature rose continuously in T above . It was projected that core temperatures associated with heat stroke (40.2 °C) would occur within 10 h. While T below was also uncompensable, the core temperature rate of rise was considerably lower than in T above such that it would take >24 h to reach 40.2 °C. Our study supports thermal-step protocols as an effective technique for evaluating survivability limits for heat exposure and provides a direct assessment of the limits of human thermoregulation.